2022
DOI: 10.4103/ijo.ijo_1009_21
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and choroidal vascular changes in newly diagnosed celiac disease: An optical coherence tomography angiography study

Abstract: Purpose: To investigate the retinal and choroidal microcirculation changes in celiac disease (CD) patients via optical coherence tomography angiography (OCT-A). Methods: This cross-sectional study included 44 pediatric patients with newly diagnosed CD and 44 healthy pediatric subjects. The vascular densities (VD) of the superficial, deep, and choriocapillar plexuses (VDs, VDd, and VDcc, respectively) (%), the superficial and deep foveal avascular zones (FAZs and FAZd) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…histopathological examination [5]. This technology has been successfully utilized in various fields such as ophthalmology [6][7][8], dermatology [9][10][11][12], oncology [13][14][15], and other areas [16][17][18]. Despite numerous experiments being carried out on the human digestive system with OCT technology, its use in identifying gastric cancer has been relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…histopathological examination [5]. This technology has been successfully utilized in various fields such as ophthalmology [6][7][8], dermatology [9][10][11][12], oncology [13][14][15], and other areas [16][17][18]. Despite numerous experiments being carried out on the human digestive system with OCT technology, its use in identifying gastric cancer has been relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“… 22 The limitation of LST is that it measures only the velocity and not the diameter of the vessel; hence, it cannot be used to study volumetric blood flow. 23 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, associated nutritional deficiency, anemia, background diabetes, hypertension, and chronicity of disease also tend to be responsible for vascular alterations. [ 1 7 8 9 ]…”
mentioning
confidence: 99%
“…The associated autoimmunity has been linked to endothelial dysfunction and hyperglobulinemia-related rheological changes. Angio imaging studies of the maculae in patients with celiac disease have reported decreased capillary density in the superficial and deep capillary plexus of the retina with an associated increase/decrease in choroidal thickness;[ 6 9 ] however, the choroidal vascularity index remains unchanged.…”
mentioning
confidence: 99%